2022
DOI: 10.1609/aaai.v36i9.21244
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Spurious Correlation for Out-of-Distribution Detection

Abstract: Modern neural networks can assign high confidence to inputs drawn from outside the training distribution, posing threats to models in real-world deployments. While much research attention has been placed on designing new out-of-distribution (OOD) detection methods, the precise definition of OOD is often left in vagueness and falls short of the desired notion of OOD in reality. In this paper, we present a new formalization and model the data shifts by taking into account both the invariant and environmental (sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…While Ming, Yin, and Li (2022) do not see success in combining nuisance information with domain generalization algorithms over their baseline ERM solution, Table 1 shows that nuisance-aware OOD detection succeeds over nuisanceunaware ERM. On non-SN-OOD inputs, reweighting yields consistent or better output-based detection performance, and reweighting plus joint independence generally yields compa-AUROC ↑ ERM (Ming) Figure 4: On Waterbirds, using the outer patch as nuisance (patch) yields comparable results to utilizing the exact environment label (exact), which requires external information beyond the image.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…While Ming, Yin, and Li (2022) do not see success in combining nuisance information with domain generalization algorithms over their baseline ERM solution, Table 1 shows that nuisance-aware OOD detection succeeds over nuisanceunaware ERM. On non-SN-OOD inputs, reweighting yields consistent or better output-based detection performance, and reweighting plus joint independence generally yields compa-AUROC ↑ ERM (Ming) Figure 4: On Waterbirds, using the outer patch as nuisance (patch) yields comparable results to utilizing the exact environment label (exact), which requires external information beyond the image.…”
Section: Methodsmentioning
confidence: 94%
“…Waterbirds. Following Ming, Yin, and Li (2022), we use the Waterbirds dataset generation code from Sagawa et al (2020), generating a different dataset for each correlation strength. We give the validation set the same correlation as the training set, rather than balancing it as done in Sagawa et al (2020).…”
Section: Experimental Set Up Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is shown that grouping the labels for in-distribution data can be effective in OOD detection for large semantic space. In(Ming, Yin, and Li 2022), the effect of spurious correlation is studied for OOD detection. Huang, Geng, and Li derived a scoring function termed GradNorm from the gradient space.…”
mentioning
confidence: 99%